The Impact of Work-family Conflict, Perceived Organizational Support, Work Engagement on Professional Commitment - Hadmiatun Hadmiatun; Sigit Wibowo; Ade Irma Anggraeni (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
This study deals with discussions about work-family conflict, perceptions of organizational support, work attached to the professional commitment of istiqomaheducational institutions sambas purbalingga. This study took respondents consisting of school teachers who are under the auspices of Sambas traditional educational institutions, namely MI, SMP and MA teachers. The sample obtained in this study was collected by 88 people using probability sampling method with sampling techniques using Proportional Random Sampling. This study uses data analysis using multiple regression analysis. From the results obtained can be concluded from the negative results between work-family conflict with professional commitment but not significantly.